Economic growth and unemployment in Indonesia: A short-run and long-run analysis using the ARDL approach - Anwar, Aminuddin (Jurnal Kebijakan Ekonomi dan Keuangan, 2025)
Purpose – This study aims to analyze the dynamic aspects determining unemployment in Indonesia for the period 1994–2024.Methods – This research utilizes a time series data analysis in Indonesia using the Autoregressive Distributed Lag (ARDL) approach.Findings – The study concludes that in the long run, inflation and government expenditure have a negative impact on unemployment. Meanwhile, in the short run, the lag value of unemployment, economic growth, and inflation influence the dynamic condition of unemployment.Implication – The implications of this study are more oriented towards strengthening monetary and fiscal policies to reduce dynamic unemployment in Indonesia.Originality – This research contributes to the analysis of the dynamic aspects determining unemployment in Indonesia by using a time series data approach with ARDL. AbstrakTujuan – Penelitian ini bertujuan untuk menganalisis aspek dinamis penentu pengangguran di Indonesia untuk periode 1994 -2024.Metode – Penelitian ini menggunakan analisis data runtut waktu di Indonesia dengan menggunakan pendekatan Autoregressive Distributed Lag (ARDL).Temuan – Penelitian ini menyimpulkan bahwa pada jangka panjang inflasi dan pengeluaran pemerintah berimplikasi negatif terhadap pengangguran, sementara itu pada jangka pendek nilai lag pengguran, pertumbuhan ekonomi dan inflasi memiliki pengaruh terhadap kondisi dinamis pengangguran. Implikasi – Implikasi dari penelitian ini lebih berorientasi pada penguatan kebijakan moneter dan fiskal dalam menurunkan pengangguran dinamis di Indonesia.Orisinalitas – Penelitian ini berkontribusi terhadap analisis aspek dinamis penentu pengangguran di Indonesia menggunakan pendekatan data runtut waktu dengan ARDL.